FORMULASI KEBIJAKAN PEMBENTUKAN KURIKULUM MUATAN LOKAL BUDIDAYA DAN AGRIBISNIS JAGUNG - Nugroho, Lucky Dafira; Pawestri, Aprilina; Wardhani, Indah Setyo (Faculty of Law, Parahyangan Catholic University, 2020)
This article addressed the question, from a juridical empirical approach) to what extent the making and implementation of a new curriculum at formal educational institution at Madura containing lesson for the preservation and development of local corn cultivation and agriculture may have positive impact on the enhancement of the local economy. Field study is conducted at the Sumenep district. The main finding is that the regional autonomy policy opens up the possibility for regional/local government to make and implement educational policy introducing a new curriculum containing lesson in local corn cultivation and corn agribusiness. This new curriculum may be implemented at the basic school up to the intermediate level with the purpose of strengthening local culture, i.e., traditional corn cultivation. With that in mind a regional regulation should be issued providing the legal basis for the above policy.